2018
DOI: 10.3168/jds.2017-13417
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Shigella sonnei-induced epithelial barrier disruption by surface-layer associated proteins of lactobacilli from Chinese fermented food

Abstract: Surface-layer associated proteins (SLAP) of Lactobacillus paracasei ssp. paracasei M5-L and Lactobacillus casei Q8-L were examined to identify the functional basis for their protection within intestinal epithelial cells. The results showed that SLAP of M5-L and Q8-L remained active in a trypsin solution and retained a 45-kDa protein band, similar to that observed in controls. In contrast, under conditions of simulated gastric juice, the SLAP were partially degraded. Inhibitory effects of SLAP on adherence of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Consistent with our results, the abnormal expression and localization of occludin and ZO‐1 were improved by heat‐inactivated mixed Lactobacillus , so as to alleviate the symptoms of intestinal leakage caused by an inflammatory factor mixture 28 . Furthermore, surface‐related proteins of Lactobacillus paracasei and Lactobacillus casei responded to membrane damage induced by Shigella sonnei by restoring the expression of ZO‐1 29 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with our results, the abnormal expression and localization of occludin and ZO‐1 were improved by heat‐inactivated mixed Lactobacillus , so as to alleviate the symptoms of intestinal leakage caused by an inflammatory factor mixture 28 . Furthermore, surface‐related proteins of Lactobacillus paracasei and Lactobacillus casei responded to membrane damage induced by Shigella sonnei by restoring the expression of ZO‐1 29 …”
Section: Discussionsupporting
confidence: 88%
“…28 Furthermore, surface-related proteins of Lactobacillus paracasei and Lactobacillus casei responded to membrane damage induced by Shigella sonnei by restoring the expression of ZO-1. 29 Abundant studies have shown that TNF-⊍ may stimulate intestinal barrier damage via inducing an imbalance in the secretion of inflammatory factors. 22 IL-8, as a pro-inflammatory factor, was responsible for regulating inflammatory response and TJ function.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [27] demonstrated that the surface-layer associated proteins (SLAP) of L. paracasei ssp. paracasei M5-L and L. casei Q8-L protect the bacteria-mediated epithelial barrier disruption by suppressing the occludin production and inhibiting the delocalization of zonula occludens-1.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of Lactobacilli, probiotic bacteria, are greater against invasive bacteria such as S. sonnei, when compared to non-invasive bacteria such as Vibrio cholerae (34). However, the mechanism of the inhibitory effect of lactic acid bacteria on Shigella has been mostly investigated in vitro (35,36), and it is not fully understood how these inhibitory effects are exerted on pathogenic bacteria in the complex intestinal microecological environment. These inhibitory effects may be associated with decreases in host gene expression, microRNA regulation and a substantial reshaping of the Listeria-monocytogenes transcriptome (37).…”
Section: Discussionmentioning
confidence: 99%